1981
DOI: 10.1139/f81-032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sympatric Dwarf and Normal Populations of Least Cisco (Coregonus sardinella) Inhabiting Trout Lake, Yukon Territory

Abstract: A normal (205– to 340-mm fork length at maturity) and a dwarf (85– to 135-mm fork length at maturity) form of least cisco (Coregonus sardinella) exist sympatrically in Trout Lake, Yukon Territory. Dwarf ciscoes have significantly fewer gill rakers, lateral lines scales, and pyloric caeca and significantly more vertebrae, on the average, than normal ciscoes. Dwarf cisco mature earlier than normals (age 3 vs. age 6); however, normals are longer lived (maximum age 23 vs. age 14) and may produce nearly 30 times th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…Their niche location represented a midrange of carbon values and relatively elevated trophic position, and their broad foraging pattern indicated that this species linked energy sources from across habitats and transferred that energy up trophic levels (Schindler & Scheuerell, 2002;Vander Zanden & Vadeboncoeur, 2002). Similar to large least cisco in ACP lakes, mature least cisco (>250 mm FL) in Trout Lake, Yukon Territory consumed an omnivorous diet of benthic invertebrates, surface insects and fish (Mann & McCart, 1981). Ontogenetic shifts in these fishes should expand and shift the dietary and isotopic niche to incorporate large crustaceans, snails, and fish as they grow (Hammerschlag-Peyer, Yeager, Araújo, & Layman, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Their niche location represented a midrange of carbon values and relatively elevated trophic position, and their broad foraging pattern indicated that this species linked energy sources from across habitats and transferred that energy up trophic levels (Schindler & Scheuerell, 2002;Vander Zanden & Vadeboncoeur, 2002). Similar to large least cisco in ACP lakes, mature least cisco (>250 mm FL) in Trout Lake, Yukon Territory consumed an omnivorous diet of benthic invertebrates, surface insects and fish (Mann & McCart, 1981). Ontogenetic shifts in these fishes should expand and shift the dietary and isotopic niche to incorporate large crustaceans, snails, and fish as they grow (Hammerschlag-Peyer, Yeager, Araújo, & Layman, 2011).…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, inter-population variation in size structure is common. Despite considerable interest in this particular aspect of population structure (e.g., Mann and McCart 1981;Diana 1987;Jansen 1996;Ylikarjula et al 1999), we lack a clear understanding of the underlying mechanism(s), particularly in relation to the ways in which the ecology and life history of organisms might interact to influence body size.…”
Section: Introductionmentioning
confidence: 99%
“…Congeneric competition -especially between sympatric forms of whitefish or sympatric forms of cisco -has been proposed as a factor in the Coregonus dwarfing phenomenon in several lakes (Svardson 1950, Fenderson 1964, Lindsey 1981, Mann & McCart 1981, Bernatchez & Dodson 1990. However, this cannot fully explain the dwarfing of the Ten Mile Lake cisco.…”
Section: Congeneric Competitionmentioning
confidence: 99%
“…The selective factors and the mechanisms involved in the establishment and maintenance of dwarf populations of lacustrine Coregonus are unknown; however, dwarf Coregonus may be recognized by a suite of typical characters. Although the most obvious trait of dwarf Coregonus is their small maximum adult size, these populations are also characterized by significant alterations in their life histories (Fenderson 1964, Mann & McCart 1981. Unlike fish in stunted populations (Heath & Roff 1987) dwarf Coregonus typically have normal rates of growth prior to maturation, undergo precocial maturation, have a shortened life span, and often exhibit a temporal shift in their spawning seasons (Svardson 1950, Fenderson 1964, Mann & McCart 1981.…”
Section: Introductionmentioning
confidence: 99%